Supplement of exogenous inorganic pyrophosphate inhibits atheromatous calcification in Apolipoprotein E knockout mice - Wenjiao Gu; Yujie Wei; Yu Tang; Shining Zhang; Shuangyi Li; Youming Shi; Fenxia Tang; Ali Mohamed Awad; Xiaowei Zhang; Futian Tang (Heliyon, 2023)
Inorganic pyrophosphate (PPi) is the endogenous inhibitor for vascular calcification (VC). The present study was to investigate the effects of adenosine disodium triphosphate (ADTP) and alendronate sodium (AL), two exogenous PPi sources, on the atheromatous calcification (AC) in Apolipoprotein E knockout (ApoE KO) mice. ApoE KO mice were randomly divided into five groups: ApoE KO group, ApoE KO + ADTP (Low) group, ApoE KO + ADTP (High) group, ApoE KO + AL (Low) group and ApoE KO + AL (High) group. The mice in ApoE KO + ADTP (Low) group and ApoE KO + ADTP (High) group were intraperitoneally injected with ADTP with dose of 0.5 and 1.0 mg/kg/day for 2 months respectively. The mice in ApoE KO + AL (Low) group and ApoE KO + AL (High) group were intraperitoneally injected with AL with dose of 0.6 and 1.2 mg/kg/day for 2 months respectively. The age matched C57 mice were used as control group. All ApoE KO and C57 mice were fed with normal chow throughout the experiment. The calcification was evaluated using von Kossa method. The contents of PPi, triglyceride (TG), total cholesterol (TC), high density lipoprotein (HDL) and low density lipoprotein (LDL), tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), interferon-γ (IFN-γ) and interleukin-10 (IL-10) as well as the activity of alkaline phosphatase (ALP) in serum were measured. The results showed that compared with C57 mice, ApoE KO mice developed severe AC accompanied with high levels of TC, TG, LDL, IL-6, TNF-α and IFN-γ in serum and with low levels of PPi and IL-10 in serum. Both ADTP and AL dose-dependently reduced the AC in ApoE KO mice compared with that of ApoE mice, without affecting the contents of lipid profiles. In addition, ADTP and AL increased the contents of PPi and IL-10 while decreased the contents of TNF-α, IL-6 and IFN-γ in serum of ApoE KO mice, having no affection on ALP activity. The results suggested that ADTP and AL reduced AC in ApoE KO mice by increasing the PPi level and regulating the inflammation.